Molecular recognition in olfaction. Issue 3 (4th May 2017) - Horsfield, A. P.; Haase, A.; Turin, L.
Abstract : The mechanism by which the chemical identity of odourants is established by olfactory receptors is a matter of intense debate. Here we present an overview of recent ideas and data with a view to summarising what is known, and what has yet to be determined. We outline the competing theories, and summarise experimental results employing isotopes obtained for mammals, insects, and individual receptors that enable us to judge the relative correctness of the theories. Graphical Abstract: